ACHIEVEMENT MOTIVATION SEBAGAI PREDIKTOR ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN DI PT. X KOTA SURAKARTA - Yoshua Aditya Wisnu Pradana ,; Sutarto Wijono , (Journal of Innovation Research and Knowledge, 2024)
Currently, Indonesia has entered the era of the Industrial Revolution 4.0, where during this industrial revolution digital technology is becoming increasingly massive. Along with the development of challenges in the industrial world, companies must be able to run their business by increasing human resources and the quality of job training for employees so that human resources become skilled so they are able to provide optimal performance. Organizational Citizenship Behavior is an important aspect for companies, because by having Organizational Citizenship Behavior employees are appointed in work results that can be beneficial for the organization such as employees will be more likely to follow the rules that apply in the company, have persistence in carrying out work with initiative that arises from an employee's personality. , Organizational Citizenship Behavior can influence many variables, one of which is Achievement Motivation. The purpose of this research is to determine the role of achievement motivation as a predictor of organizational citizenship behavior in employees at PT. X Surakarta. In this research, quantitative research methods are used as research methods. This research uses a sample of 100 people from the population using a simple random sampling probability technique, where the selection of samples from a population is based on the principle of randomization or chosen by chance. The estimation instrument in this study uses the Achievement Motivation scale compiled by McClallend (1987), then for To measure organizational citizenship behavior variables, the authors used a scale adapted by Organ et al., (2006). In hypothesis testing, the results obtained were R2 = 11.197: p<0.05. These results mean that Achievement Motivation is a predictor of Organizational Citizenship Behavior.